2021
DOI: 10.3390/toxins13090608
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Acupuncture Effects on Pain and Its Mechanisms: An Updated Review

Abstract: Bee venom (BV) is a complex natural toxin that contains various pharmaceutical compounds. Bee venom acupuncture (BVA), involving a BV injection into a certain acupuncture point, has been utilized to relieve a range of pain conditions. Regardless of whether pain is caused by disease or injury, if not effectively treated, pain can exert a detrimental effect on all aspects of life. In the past decade, many researchers have investigated the anti-nociceptive effects of BVA through clinical use and experimental eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
(191 reference statements)
0
2
0
Order By: Relevance
“…Most studies, including RCTs and reviews, were related to acupuncture treatment for shoulder pain. Some of these included studies reported that acupuncture is effective in relieving shoulder pain, 43,44 whereas others did not mention whether it is effective or ineffective in treating shoulder pain 26 or whether it is ineffective in treating shoulder pain; 45 Different acupuncture methods or tools have been used in studies on acupuncture to treat shoulder pain, such as bee venom acupuncture, 46 auricular acupuncture, 47 fire needles, 48,49 small needle-knife, 41 thread-embedding acupuncture, 50 warm-needle moxibustion and heat-sensitive moxibustion, 6 electroacupuncture, 51 and sharp-hook acupuncture. 52 Some studies are related to summarizing the common acupoints rules of acupuncture treating and moxibustion in shoulder pain, such as Tiaokou; 53 Chengshan acupoint; 54 Baihui acupoint; 55 Ashi points stimulation; 56 Zhongfu, Tianfu, Xiabai, Binao, Naohui, Jianliao, and Xiaoluo points; 57 distal-needling acupuncture; 58 and acupuncture on the opposite side of the pain to treat long-term shoulder pain.…”
Section: Current Research Hotspots and Frontiersmentioning
confidence: 99%
“…Most studies, including RCTs and reviews, were related to acupuncture treatment for shoulder pain. Some of these included studies reported that acupuncture is effective in relieving shoulder pain, 43,44 whereas others did not mention whether it is effective or ineffective in treating shoulder pain 26 or whether it is ineffective in treating shoulder pain; 45 Different acupuncture methods or tools have been used in studies on acupuncture to treat shoulder pain, such as bee venom acupuncture, 46 auricular acupuncture, 47 fire needles, 48,49 small needle-knife, 41 thread-embedding acupuncture, 50 warm-needle moxibustion and heat-sensitive moxibustion, 6 electroacupuncture, 51 and sharp-hook acupuncture. 52 Some studies are related to summarizing the common acupoints rules of acupuncture treating and moxibustion in shoulder pain, such as Tiaokou; 53 Chengshan acupoint; 54 Baihui acupoint; 55 Ashi points stimulation; 56 Zhongfu, Tianfu, Xiabai, Binao, Naohui, Jianliao, and Xiaoluo points; 57 distal-needling acupuncture; 58 and acupuncture on the opposite side of the pain to treat long-term shoulder pain.…”
Section: Current Research Hotspots and Frontiersmentioning
confidence: 99%
“…Bee venom pharmacopuncture (BVP) is a treatment method used in traditional East Asian medicine. The method involves the injection of venom extracted and processed from the venom sac of honeybees into an acupoint or intramuscular pressure point associated with disease for therapeutic purposes [ 1 , 2 , 3 ]. Although BVP is used for the treatment of musculoskeletal disorders as well as various other diseases, some components in the body act as antigens and can cause life-threatening adverse events (AEs), such as anaphylaxis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%